El contador Geiger como herramienta en la enseñanza del concepto de radiación - Ramírez Arias, Leonardo; Uribe Cortés, Julian (Góndola, enseñanza y aprendizaje de las ciencias, 2007)
This proposal is based on the realization of a didactic module that raises experimentation as a strategy to introduce high school students in subjects of modern physics. We work topics such as radiations in a way of approaching problems that students investigate and develop in various activities. A tool is offered to the teacher to be able to propose a methodology that motivates and causes different expectations in students for science. The development of this module is based on the manipulation of the Geiger counter measuring different emissions that occur in natural environments.